De-‘Moor’ tifying Shakespeare’s Othello: Iago as a Renaissance form of Islamophobia - Ismail, Hanita Hanim; Ali Termizi, Arbaayah; Ab Rashid, Radzuwan (Canadian Center of Science and Education, 2018)
Albeit Othello’s loyal service to Venice is clear, ramifications of the Blackamoor in the text has called upon a continuous scholarship of interest over the last two decades. One begins to wonder, whether the Blackamoor’s presence in a Venetian setting serves a purpose to the English readership? If so, to what extent did Shakespeare refine the representation of a Moor to draw upon readership? How does Iago serve as a propagandist who articulates and fuels concerns for the seventeenth-century version of Islamophobia? As such, these significant questions have led to the construction of this paper, since these issues continuously problematize and make relevance of Shakespearean plays in the contemporary world. As such, this article examines the significance of Shakespeare’s inclusion, portrayal and representation of Othello as a Moor that poses an image of threat in a seventeenth-century Western context. At the same time, this paper also asserts that Iago is the mouthpiece who initiates worries over possible threats of Islamophobia. The use of Greenblatt’s New Historicism, particularly his concept of energia (1988) enables the validation of such claims by making relevance of the Battle of Lepanto (1571). Results indicated that ‘Othello’ provides an important platform to discuss contemporary renaissance issues such as Islamophobia and Englishness, through indicative clues that Iago is the mastermind that causes fear of the advancing Moors.